Neuroglia (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This book is a compiled version of the journal Neuroglia. It was a peer-review Open Access journal by MDPI that investigated a wide range of glia related topics. Now the journal is published as a section of the journal Brain Sciences, with a new section Editor-in-Chief Prof. Sergey Kasparov.